Early grade reading: The experience of Donaberber full cycle primary school in providing opportunities to learn - Haileyesus Wudu Mekonnen (College of education, Bahir Dar University, 2023)
The purpose of this study was to explore the experiences of Donaberber Full Cycle Primary School in providing students foundational opportunities enabling them to read in their early grade (grade 1). All teachers (n= 7) assigned to teach grade one students, 2 school principals, and randomly selected 56 (out of 273) first-grade students participated in the study. Data were collected through observation, interviews, document analysis, and focus group discussion. Weft-QDA software was used to conduct a qualitative analysis of the information gathered from observation, interviews, and focus group discussions in order to identify overarching themes. Data from document analysis were analysed quantitatively. The study found that spending available resources differently, the school employed effective and efficient utilization of OTL. Specifically, the investigation revealed that there was an optimal use of instructional time, meaning that students were given maximum instructional time for reading, and reading was the instructional priority for the first three months of the school year, and the school applied an innovative pedagogy. The way the school provided students with foundational opportunities to read early within a few months is a good experience from which others could learn.